User interface based on natural interaction design for seniors. - Hsiao, Shih-Wen; Lee, Chu-Hsuan; Yang, Meng-Hua; Chen, Rong-Qi (Computers in Human Behavior, 2017)
With world population ageing, how to help seniors to adapt to technology life is an important issue. Technology is becoming life rather than resistance, because many of the technology applications are often accompanied by a lot of information to process. This makes the user interface to become an important bridge between human computer interactions. Especially the inconvenience caused by human ageing, these related issues from the cognitive and operational of products are derived. This study proposes a study of user interface design based on natural interaction to increase seniors’ usage intention. In the proposed contents, the Kinect sensor is used to retrieve seniors’ in-depth information in movements, thus the user interface of system can be operated by the gesture intuitively. In the framework of the system, in the first all, the morphology is applied to identify the features of a hand from depth values obtained from the sensor. Gesture is used to recognize operating behavior of users to implement the interactive action, and collision detection is applied to confirm effectiveness of operation. On the other hand, through interpretive structural model (ISM), each design element of interactive interface can be decomposed and realized, and the solution for target and direction of design problem is also proposed. At the meanwhile, the concept of affordance is conducted to the development of interface for graphic users that proposed in this study, and the design achievement contains operation and usability of intuition can further be acquired. Finally, based on the proposed methodology, an intuitive user interface of digital devices is constructed by Java programming language that allows for verifying the feasibility of user interface for seniors. Besides, the proposed method can be widely used to develop the user interface for various products.